Judo as a Work of Art: Exploring Aesthetic Dimensions in Sport - Shorkend D (New Ideas Concerning Arts and Social Studies Vol. 1, 2025)
Judo, according to the translation of the meaning of the Japanese language "gentle way", "gentle means", or "The Way of softness and flexibility. In this study, an argument was introduced that the first principles inherent in art, that is its formal components such as line, colour, composition and so on can be viewed as mechanisms enabling a deeper aesthetic appreciation of sport. In this particular case the sport looked at is judo. One could claim that in art the extrinsic aim is to create a work, a particular body, as it were whereas in sport this is not the explicit aim. Furthermore, art is neither agonistic nor pragmatic in the way sport is, where the intrinsic aim is not merely the work or performance itself but the tallying of points in a clearly defined manner toward victory. If this thesis is correct, it implies an interdisciplinary field of study traversing art and sport, the humanities and the sciences and overturns the old Cartesian dualism in favor of a more integrated embodied experience.